2016
DOI: 10.1097/md.0000000000005492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral health behavior and sociodemographic factors on remaining teeth in Korean adults

Abstract: In this study, the number and location of remaining teeth were analyzed according to sociodemographic variables, anthropometric measurements, and oral health behavior patterns. The hypothesis was that the number and location of remaining teeth would be affected by oral health behavior and by sociodemographic factors, such as education levels, household income, and urban/rural residency.This nationwide cross-sectional study was performed with a total of 36,026 representative Korean adults aged 19 and older. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
11
1
2
Order By: Relevance
“…The number of remaining teeth of ENSs increases with increase in the daily toothbrushing frequency (Table 2). This result was in line with that observed in a Korean study (Song, Han, Choi, Ryu, & Park, 2016) where the number of remaining teeth means increased from 16.5 ± 0.5 in nonbrushers to 23.8 ± 0.1 in brushers of more than four toothbrushings per day.…”
Section: Discussionsupporting
confidence: 92%
“…The number of remaining teeth of ENSs increases with increase in the daily toothbrushing frequency (Table 2). This result was in line with that observed in a Korean study (Song, Han, Choi, Ryu, & Park, 2016) where the number of remaining teeth means increased from 16.5 ± 0.5 in nonbrushers to 23.8 ± 0.1 in brushers of more than four toothbrushings per day.…”
Section: Discussionsupporting
confidence: 92%
“…First, the results may differ in other regions and in participants with different characteristics because (i) all study participants were residents of Incheon, where the socioeconomic status is relatively high; (ii) the sample was small; and (iii) most participants were women. Although the number of remaining teeth has been typically reported to differ by sex, no sex difference was found in the current study. A systematic review showed that gender differences in the number of remaining teeth have narrowed over the past 20 years and were not significant recently.…”
Section: Discussioncontrasting
confidence: 80%
“…Interestingly, we also identified two less expected risk factors: being female and brushing teeth more than once a day. A nationwide study of 36,026 Korean adults found that women brushed their teeth more often than men did, but men retained more natural teeth than women [28]. There is no doubt that brushing teeth is important for maintaining oral health.…”
Section: Discussionmentioning
confidence: 99%